Association of alterations in smell and taste with depression in older adults. Issue 2 (21st February 2018) - Hur, Kevin; Choi, Janet S.; Zheng, Melissa; Shen, Jasper; Wrobel, Bozena
Abstract : Objective: Examine the relationship between depression and changes in smell or taste. Study Design: Cross‐sectional analysis of 2011–2012 and 2013–2014 National Health and Nutrition Examination Survey (NHANES). Methods: We examined 5, 275 adults ≥40 years old who completed smell and taste questionnaires as well as a validated depression assessment instrument, the Patient Health Questionnaire (PHQ‐9). Analyses incorporated sampling weights to account for the complex sampling design and associations were analyzed using multivariate logistic regression adjusted for related demographics and socioeconomic data. Results: The prevalence of altered smell and taste was 23.0% (95% CI: 20.7–25.3%) and 11.9% (95% CI: 10.7–13.1%), respectively. Among those who met criteria for major depressive disorder, the prevalence of altered smell and taste was higher at 39.8% (95% CI: 33.4–46.1%) and 23.7% (95% CI: 18.7–28.7%), respectively. In a multivariate model adjusting for age, gender, education, major comorbidities, smoking history, heavy alcohol use, sinus disease, cold symptoms, and trauma history, adults ≥40 and <65 years old who reported alterations in smell (OR: 1.64, p  = 0.004) and adults ≥40 years old who reported alterations in taste (OR: 1.77, p  = 0.001) were more likely to meet criteria for major depressive disorder. Conclusion: There is a strong association between major depression and alterations in smell and taste among certain age groups in the general U.S. population. Primary care providers should screen for depression when patients report changes in smell or taste. Level of Evidence: 4.